Burden of corticosteroid use in patients with systemic lupus erythematosus: results from a Delphi panel. (September 2014) - Petri, M; Bechtel, B; Dennis, G; Shah, M; McLaughlin, T; Kan, H; Molta, C
Corticosteroid-related adverse events (AEs) are commonly reported in systemic lupus erythematosus (SLE), but are often under-represented in claims data. The most common corticosteroid-related AEs are not necessarily the most costly. The present study aimed to examine corticosteroid-related AE rates and identify the associated cost consequences in patients with SLE from the perspective of rheumatologists treating SLE in the United States (US). A modified Delphi process and RAND Appropriateness Method was used to estimate corticosteroid-related AEs and costs based on data from SLE-treating US rheumatologists and estimates from alternative sources. The panel ( n = 10) participated in two web-based questionnaires, covering disease severity, corticosteroid use, corticosteroid-related AEs, and resource utilization associated with treatment of the AEs. Eight members of the panel then participated in a guided discussion by interactive teleconference, in which the costs associated with specific corticosteroid-related AEs were also discussed. Consensus was achieved in the teleconference when a single response category (consensus values from 1 to 4 [4 = strongly agree, 1 = strongly disagree]) accounted for ≥80% of responses. Thirteen consensus statements were developed following two Delphi rounds. Costs were estimated for eight corticosteroid-associated AEs from the panel of rheumatologists. In the patients with SLE treated by these physicians, 41.5% were considered to have mild disease, 36.5% moderate disease, and 22.0% severe disease. The number of specialist visits, corticosteroid use, and corticosteroid dose increased with disease severity. The estimated rates of all AEs (except for cataracts) were at least doubled in patients receiving corticosteroid doses >20 mg/day compared with ≤20 mg/day. The highest estimated mean total costs of an event (for the required treatment duration for one patient) were for avascular necrosis (14, 460) and serious infection (11, 660). The costs of more common AEs, such as osteoporosis, obesity, diabetes, and fractures, ranged from 1190 to 8220. Ten rheumatologists concluded that as disease severity increases, corticosteroid doses increased. Greater utilization of resources is needed to manage patients and corticosteroid-related AEs.